2019
DOI: 10.4103/jfmpc.jfmpc_314_18
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of the student nurses of a tertiary health-care center – A mixed-method study

Abstract: Context: Nursing students are the future role model of health; so critical evaluation of their nutritional status is imperative for effective functioning of health sector. Aims: The aim is to assess the nutritional status of nursing students using basal metabolic index and exploring the causes of malnutrition along with uncovering the causes behind these causes of malnutrition. Setting and Design: Nutritional status of student's nurses was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…In our study, 101 (56.1%) consumed green leafy vegetables two times or less per week, out of which 41.5% were found to be anemic, while for those who consumed three or more in a week, 41.7% were anemic. Hadaye et al reported similar decreased compliance toward healthy eating in their study at a tertiary care hospital in Mumbai, India, in which 70 out of 280 students (25%) consumed green leafy vegetables only once a week [ 13 ]. Although the diagnosis of anemia is simple, it goes unnoticed for a prolonged duration due to its non-specific clinical signs and a lack of testing and patient education on the symptoms of anemia.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, 101 (56.1%) consumed green leafy vegetables two times or less per week, out of which 41.5% were found to be anemic, while for those who consumed three or more in a week, 41.7% were anemic. Hadaye et al reported similar decreased compliance toward healthy eating in their study at a tertiary care hospital in Mumbai, India, in which 70 out of 280 students (25%) consumed green leafy vegetables only once a week [ 13 ]. Although the diagnosis of anemia is simple, it goes unnoticed for a prolonged duration due to its non-specific clinical signs and a lack of testing and patient education on the symptoms of anemia.…”
Section: Discussionmentioning
confidence: 96%
“…India has an average of 1 nurse for every 2500 residents, compared with 1 for every 150–200 in developed countries. [ 3 ] It is a stressful profession with a lot of workload, which may have ill effects on the physical and psychological well-being of an individual’s health. [ 4 ] The job of nurses requires working in irregular shifts along with bearing heavy physical and psychological demands, which, in turn, risk their overall health status.…”
Section: Introductionmentioning
confidence: 99%